Effect of stance width on posture stability of golfers putting under windy conditions - Yang, C.-J.; Tai, M.-L.; Hu, C.-M.; Hamill, J.; Tang, W.-T. (International Journal of Sports Science & Coaching, 2021)
Golf putting requires accuracy and precision. However, environmental factors can influence the accuracy and stability of the putt. Therefore, the purpose of this study was to investigate the adjustment and stabilization strategies of elite college golfers putting under different wind conditions. A 3 D motion analysis system and two force plates were used to record the kinematic and ground reaction force data of the putting stroke in different conditions of wind and putting stance. The artificial wind was produced from an industrial negative pressure fan to create different wind speeds. Participants were asked to perform three putts to the `virtual` hole with a distance of 15 feet under three wind speeds (none, mid, strong) and three stance width conditions. The results revealed that distance control in strong wind conditions was significantly worse. No significant improvement was found in either distance or direction control when using different stance widths for putting under varying wind speeds. While putting under minor or moderate wind conditions, the player can adjust through self-adjustment on movement control to reduce the impact of external wind on putting performance. However, if the wind speed exceeds to certain threshold value (5.5 m/s), the challenges for golfers to maintain postural stability along the antero-posterior axis increased and led to poor putting distance control. Our results suggest that when putting under windy conditions, elite low-handicap college golfers are able adopt a normal stance in order to minimize a change in their putting protocol.